The use of species of commelina as feed for field cricket, scapsipedus icipe (orthoptera: gryllidae) - Irakiza, Runyambo (Jooust, 2023)
Sub-Saharan Africa faces persistent challenges in reducing malnutrition and enhancing food security. The field cricket, Scapsipedus icipe Hugel and Tanga (Orthoptera: Gryllidae), is edible and could be used to alleviate malnutrition. Currently, there is limited knowledge on what plants this insect feeds on as natural diets source of proteins for mass rearing. This study aimed to determine the diversity of species of Commelina in different agroecological zones in Western Kenya, evaluate the feeding preferences of S. icipe for species of Commelina, and determine the optimum growing conditions for Commelina using cricket frass as manure. To determine the diversity of species of Commelina, a phytosociological method was used to collect plants using quadrats, whereas soil samples from each quadrat and managements were collected to examine the relationship between species of Commelina and soil and management. Preferences of S. icipe for species of Commelina were evaluated through no-choice, dual choices, and multiple- choice experiments conducted in a RCBD design in controlled environment. Optimum growing conditions for Commelina using cricket frass as manure were determined through experiments carried out in a screenhouse and open field environments laid in a CRD and RCBD designs, respectively. The results of the diversity showed that eleven species of Commelina were identified, with C. diffusa and C. benghalensis var. benghalensis (non-hybrid variant) having higher relative density. The results also found that the distribution of species of Commelina was significantly influenced by soil pH, available P, TN, fertility, and crop spacing. The feeding experiments showed that S. icipe had a significantly higher feeding rate on C. petersii and C. forskaolii and a significantly lower feeding rate on Commelina sp. and C. purpurea in comparison to references. There were positive significant associations between leaf feeding and Ca and NDF content of leaves and a negative significant association between Ca and NDF. A high Ca/low NDF content was recorded for C. petersii and a low Ca/high NDF content for C. purpurea. Six phytochemical constituents of the leaves influenced leaf feeding: phenols, alkaloids, tannins, glycosides, saponins and anthraquinones. Phenols stimulate feeding by S. icipe on C. petersii and C. forskaolii, whereas the tannins and alkaloids in Commelina sp. and C. purpurea, acted as deterrents. Optimum growing conditions for C. petersii were determined using cricket frass as manure, and the application rate of 15 t ha–1 of cricket frass yielded the best results. Cricket frass significantly increased the vegetative parameters (plant height, number of leaves, number of shoots, leaf area, and plant biomass) of C. petersii at 5, 10, and 15 t ha–1 compared to untreated plants. Moreover, cricket frass increased the nutrient contents of C. petersii for CP and NDF as well as of Ca at 5, 10, and 15 t ha–1 compared to untreated plants. The 15 t ha–1 provided adequate levels of CP and Ca while still maintaining a reasonable level of NDF. Using local resources such as species of Commelina and cricket frass as manure could be a sustainable way for mass production of S. icipe.
Keywords: Use of insects as feeds.; Diversity of species of Commelina in different agroecological zones in Western Kenya.; Feeding preferences of S. icipe for species of Commelina